Advances in the Surgical Management of Articular Cartilage Defects: Autologous Chondrocyte Implantation Techniques in the Pipeline. (January 2013) - Stein, Spencer; Strauss, Eric; Bosco, Joseph
Objective: The purpose of this review is to gain insight into the latest methods of articular cartilage implantation (ACI) and to detail where they are in the Food and Drug Administration approval and regulatory process. Design: A PubMed search was performed using the phrase "Autologous Chondrocyte Implantation" alone and with the words second generation and third generation. Additionally, clinicaltrials.gov was searched for the names of the seven specific procedures and the parent company websites were referenced. Results: Two-Stage Techniques: BioCart II uses a FGF2v1 culture and a fibrinogen, thrombin matrix, whereas Hyalograft-C uses a Hyaff 11 matrix. MACI uses a collagen I/III matrix. Cartipatch consists of an agarose-alginate hydrogel. Neocart uses a high-pressure bioreactor for culturing with a type I collagen matrix. ChondroCelect makes use of a gene expression analysis to predict chondrocyte proliferation and has demonstrated significant clinical improvement, but failed to show superiority to microfracture in a phase III trial. One Step Technique: CAIS is an ACI procedure where harvested cartilage is minced and implanted into a matrix for defect filling. Conclusion: As full thickness defects in articular cartilage continue to pose a challenge to treat, new methods of repair are being researched. Later generation ACI has been developed to address the prevalence of fibrocartilage with microfracture and the complications associated with the periosteal flap of first generation ACI such as periosteal hypertrophy. The procedures and products reviewed here represent advances in tissue engineering, scaffolds and autologous chondrocyte culturing that may hold promise in our quest to alter the natural history of symptomatic chondral disease.